2022
DOI: 10.3389/fbioe.2022.812507
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Assessment of Localised Corneal Biomechanical Deterioration With Keratoconus Progression

Abstract: Purpose: To evaluate the regional corneal biomechanical deterioration with keratoconus (KC) progression as measured by the Stress-Strain Index (SSI) maps.Methods: The preoperative examinations of 29 progressive KC cases that were submitted to corneal cross-linking (CXL) were evaluated. The examinations included the tomography and the SSI measured by the Pentacam HR and the Corvis ST (Oculus, Wetzlar, Germany), respectively. The results were recorded twice, the latter of which was at the last visit before the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In contrast, only mild non-significant alterations were observed outside the area of pathology ( Lopes et al, 2022 ). Martínez-Sánchez et al (2022) found that SSI decreases significantly after topical prostaglandin (PG) therapy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, only mild non-significant alterations were observed outside the area of pathology ( Lopes et al, 2022 ). Martínez-Sánchez et al (2022) found that SSI decreases significantly after topical prostaglandin (PG) therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is more promising to explore the effects of differences in the internal structure of corneal materials on biomechanics through SSI. For example, the localized aspect of the microstructure deterioration in keratoconus boosted the need to map the corneal stiffness to identify the regional biomechanical failure through SSI ( Lopes and Elsheikh, 2022 ; Lopes et al, 2022 ). In that regard, it has been observed through SSI maps that the regional deterioration in stiffness was concerted inside the pathological keratoconus region.…”
Section: Discussionmentioning
confidence: 99%